Thermal expansion and polarization behavior in lead Titanate/Zinc Oxide nanocomposite ceramics - R. Wongmaneerung (2018)
This study examined nanosized zinc oxide/lead titanate (ZnO/PT) ceramic matrix nanocomposites. Under an appropriate sintering condition, ZnO/PT ceramic nanocomposites were successfully fabricated using a pressureless sintering technique. Thermal expansion and polarization behaviors were determined by using a dilatometer. This technique measures the temperature- dependence of the strain, and the magnitude of polarization can be deduced from the sets of thermal expansion data. The calculated electric polarization values on the ZnO/PT nanocomposite ceramics demonstrated a simple approach to determine the temperature dependence of the polarization below and around the transition temperature. Various aspects of understanding the polarization behavior and other effects in the ferroelectric are discussed. Copyright © 2013 Trans Tech Publications Ltd.